(untitled) - Rose, Jeneva ([Cambridge, United Kingdom], 2020)
"Sarah Morgan is a successful and powerful defense attorney in Washington D.C. As a named partner at her firm, life is going exactly how she planned. The same cannot be said for her husband, Adam. Hes a struggling writer who has had little success in his career and he tires of his and Sarahs relationship as she is constantly working. Out in the secluded woods, at the couples lake house, Adam engages in a passionate affair with Kelly Summers. But one morning everything changes. Kelly is found brutally stabbed to death and now, Sarah must take on her hardest case yet, defending her own husband, a man accused of murdering his mistress"--
Keywords: Fiction; Investigation; Murder; Mistresses; Fiction; Adultery; Fiction; Marital conflict; Fiction; Women lawyers; Fiction; Crimes against; Psychological fiction; Thrillers (Fiction); Legal fiction (Literature); Novels